Հայոց ազգածագման խնդիրն ըստ վերջին հնածինական ուսումնասիրութիւնների - Պետրոսեան, Արմէն; Պալեան, Արամ (տպ. Atlas)
Basing their work on the latest paleogenetic findings, the authors propose a new theory on the origins of the Armenian nation. The authors argue that the proto-Armenian language originated in the birthplace of Indo-European languages, in the steppe and forest belt between the Pontus and the Caspian Sea. It could not have started anywhere else because that is the place where other Indo-European languages which come closest to the Armenian language, like the Greek, Indo-lranian and Baltic-Slavonic languages, were formed. During the middle of the 3rd millennium, the bearers of the proto-Armenian language crossed to the Caucasus and initially settled in the northern and eastern regions of the Armenian Highland. They and their descendants are the ones who created the Middle and Late Bronze Age and Iron Age cultures in the Armenian Highland. As of the later part of the Middle Bronze Age, Etyuni became the primordial and central Armenia of the proto-Armenians. (Basically the central area of Mets Наук, the Ayrarat District, was called Etyuni in Urartian inscriptions). The other two hypotheses on the origins of the Armenian nation, the Balkan and Hayasa theories, have been refuted lately through paleogenetic data. In time, the steppe Indo Europeans (the proto-Armenians) were mixed with the local inhabitants, though the steppe element continued to dominate for a long time in the paternal hereditary mode. Until the fall of Urartu (6th century BC) the steppe-originated R1b and 12 haplogroups of the Y chromosome constituted 75% of the population of Etyuni. Gradually this percentage fell, though among current Armenians these haplogroups constitute some 30% of the total, while among the Armenians of the Eastern regions (Artsakh, Sunik and the plain of Ayrarat) they constitute about 40%.
Keywords: Ազգագրութիւն; Ծագումնաբանութիւն